Deadline - Crutcher, Chris (Greenwillow Books, 2007)
Given the medical diagnosis of one year to live, high school senior Ben Wolf decides to fulfill his greatest fantasies, ponders his life's purpose and legacy, and converses through dreams with a spiritual guide known as "Hey-Soos."